Risk factors in pregnancy with heart disease and their co-relation with adverse feto-maternal outcome - Sharma, Preeti; Malik, Renuka; Pandit, Neeraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Heart disease complicates 1% to 3% of all pregnancies and is responsible for 10% to 15% of maternal mortality. In India, the predominant heart disease is still RHD (rheumatic heart disease), whereas in the developed countries congenital heart disease is more common. Methods: This prospective observational study conducted in Department of Obstetrics and Gynecology in carried in PGIMER and Dr. RML Hospital, New Delhi from November 2015 to March 2017. 35 patients with heart disease were included in this study eight risk factors, four non-cardiac (age, parity, BMI and time of reporting to hospital) and four cardiac risk factors (etiology of lesion, type of lesion, prosthetic valve on anticoagulation and associated cardiac complication like atrial fibrillation (AF), pulmonary edema, pulmonary artery hypertension (PAH) were co-related with predefined indicators for adverse feto-maternal outcome. NYHA class, CARPREG score, modified WHO class were also co-related with adverse feto-maternal outcome. Results: RHD is still more common than CHD in our population. No association was seen between any non-cardiac risk factor and adverse maternal outcome. Among cardiac risk factors, severe MS, severe PAH, NYHA class IV, AF, CARPREG score ≥2 were significantly associated with adverse maternal and fetal outcome. There was no maternal or fetal death in the present study. Conclusions: Severe MS, severe PAH, AF, NYHA Class IV, CARPREG score ≥2 had positive predictive value for adverse feto maternal outcome in the present study which had no maternal or fetal mortality. Need for Preconceptional counselling which was seen to be totally absent in the present study is emphasized.